IMPACT IMPACT IMPACT IMPACT IMPACT OF OF THERMAL THERMAL THERMAL THERMAL THERMAL INSULATION INSULATION INSULATION INSULATION STRATEGIESTRATEGIESTRATEGIESTRATEGIESTRATEGIESTRATEGIESTRATEGIE S - S., Benharkat1*, . Telilani2 I. (university of eloued جامعة الوادي, 2020)
in Algeria is experiencing a multi Housing in Algeria is experiencing a multi Housing in Algeria is experiencing a multi Housing in Algeria is experiencing a multi Housing in Algeria is experiencing a multiHousing in Algeria is experiencing a multi Housing in Algeria is experiencing a multiHousing in Algeria is experiencing a multi Housing in Algeria is experiencing a multi Housing in Algeria is experiencing a multiHousing in Algeria is experiencing a multi Housing in Algeria is experiencing a multi Housing in Algeria is experiencing a multiHousing in Algeria is experiencing a multiHousing in Algeria is experiencing a multi Housing in Algeria is experiencing a multi Housing in Algeria is experiencing a multi-dimensional crisis: crisis in de dimensional crisis: crisis in dedimensional crisis: crisis in de dimensional crisis: crisis in dedimensional crisis: crisis in de dimensional crisis: crisis in dedimensional crisis: crisis in de dimensional crisis: crisis in dedimensional crisis: crisis in dedimensional crisis: crisis in de dimensional crisis: crisis in de dimensional crisis: crisis in de sign sign (standa (standa rdization of housing), construction, financing, management, etc., which has a negative dization of housing), construction, financing, management, etc., which has a negative dization of housing), construction, financing, management, etc., which has a negative dization of housing), construction, financing, management, etc., which has a negative dization of housing), construction, financing, management, etc., which has a negative dization of housing), construction, financing, management, etc., which has a negative dization of housing), construction, financing, management, etc., which has a negative dization of housing), construction, financing, management, etc., which has a negative dization of housing), construction, financing, management, etc., which has a negative dization of housing), construction, financing, management, etc., which has a negative dization of housing), construction, financing, management, etc., which has a negative dization of housing), construction, financing, management, etc., which has a negative dization of housing), construction, financing, management, etc., which has a negative dization of housing), construction, financing, management, etc., which has a negative dization of housing), construction, financing, management, etc., which has a negative dization of housing), construction, financing, management, etc., which has a negative dization of housing), construction, financing, management, etc., which has a negative dization of housing), construction, financing, management, etc., which has a negative dization of housing), construction, financing, management, etc., which has a negative dization of housing), construction, financing, management, etc., which has a negative dization of housing), construction, financing, management, etc., which has a negative dization of housing), construction, financing, management, etc., which has a negative dization of housing), construction, financing, management, etc., which has a negative dization of housing), construction, financing, management, etc., which has a negative dization of housing), construction, financing, management, etc., which has a negative dization of housing), construction, financing, management, etc., which has a negative dization of housing), construction, financing, management, etc., which has a negative dization of housing), construction, financing, management, etc., which has a negative dization of housing), construction, financing, management, etc., which has a negative dization of housing), construction, financing, management, etc., which has a negative dization of housing), construction, financing, management, etc., which has a negative dization of housing), construction, financing, management, etc., which has a negative dization of housing), construction, financing, management, etc., which has a negative dization of housing), construction, financing, management, etc., which has a negative impact on user comfort, poor housing quality and high impact on user comfort, poor housing quality and high impact on user comfort, poor housing quality and high impact on user comfort, poor housing quality and high impact on user comfort, poor housing quality and high impact on user comfort, poor housing quality and high impact on user comfort, poor housing quality and high impact on user comfort, poor housing quality and high impact on user comfort, poor housing quality and high impact on user comfort, poor housing quality and high impact on user comfort, poor housing quality and high impact on user comfort, poor housing quality and high energyenergy energyenergy consumption.consumption. consumption. consumption. consumption. This article focuses on the study of impact This article focuses on the study of impact This article focuses on the study of impact This article focuses on the study of impact This article focuses on the study of impact This article focuses on the study of impact This article focuses on the study of impact This article focuses on the study of impact This article focuses on the study of impact This article focuses on the study of impact This article focuses on the study of impact This article focuses on the study of impact This article focuses on the study of impact This article focuses on the study of impact This article focuses on the study of impact This article focuses on the study of impact This article focuses on the study of impact This article focuses on the study of impact This article focuses on the study of impact different different different different thermal thermal insulation insulation str ategies ategies ategies on on energy consumptionergy consumptionergy consumption ergy consumptionergy consumptionergy consumption ergy consumption ergy consumption (heating and cooling) (heating and cooling) (heating and cooling) (heating and cooling) (heating and cooling) (heating and cooling) (heating and cooling) (heating and cooling) (heating and cooling) of a residential building of a residential building of a residential building of a residential building of a residential building of a residential building of a residential building of a residential building of a residential building of a residential building situated situated situated in semi in semi in semi -arid arid arid climate climate climate climate (Constantine (Constantine (Constantine (Constantine (Constantine -northeast of Algeria) northeast of Algeria)northeast of Algeria) northeast of Algeria) northeast
artical
Keywords: Energy consumption Energy consumptionEnergy consumption Energy consumptionEnergy consumptionEnergy consumption Energy consumption Energy consumption , residential buildings residential buildings residential buildingsresidential buildings residential buildings residential buildings , thermal thermal insulation insulation insulation insulation strategies rategies rategies